Tinjauan Yuridis Wanprestasi Terhadap Perjanjian Jual Beli Akun Vidio Premium Milik Pt Vidio Oleh Pengguna Di Media Sosial Dan Marketplace - Zaklylen, Arizkygo Zidane; Hanifah, Mardalena; Lestari, Rika (Jurnal Ilmiah Wahana Pendidikan, 2025)
Vidio Premium is a service provided by PT Vidio to watch series or sports matches. Subscribing to Vidio Premium allows users to watch exclusive video content in the form of the best selected movies and series from Indonesia and abroad, ranging from local and international sports content such as soccer, badminton, tennis, basketball, as well as original video series ranging from drama to action. This feature is generally not available to non-premium users. Article 1338 of the Civil Code stipulates that an agreement must be carried out in good faith and in Article 17 of Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions stipulates that the parties to electronic transactions must act in good faith in conducting interactions and or exchanging electronic information. So in the implementation of buying and selling Premium Videos by selling an account, it is actually not in good faith in carrying out the agreement. This type of research can be classified as normative juridical research, because this research is conducted by examining secondary data and statutory approaches. This normative research examines legal systematics. The data sources used are primary data, secondary data, tertiary data, data collection techniques in this research are normative juridical, the data used is literature study. The result of the research conducted by the author is that the sale of premium video services on social media is an act that is prohibited by law. The act of buying and selling YouTube Premium constitutes a breach of contract as it violates the terms of service of Vidio Premium. The legal consequence of this sale is a breach of contract, and dispute resolution can be pursued in court. There is a need for specific regulations regarding the buying and selling of accounts. Premium Vidio users are also advised to carefully read the terms of service for this paid Vidio premium. There should be special arrangements related to the buying and selling of Vidio premium accounts. Additionally, there should be warnings and sanctions imposed by Vidio on individuals who sell Vidio premium accounts, as well as regular checks on the addresses of Vidio account users to protect the interests of all parties involved.